Conditions facilitating faculty members’ implementation of online learning technology in Iranian universities - Razavi, M. R.; Mahmud, Rosnaini; Wan Ali, Wan Zah; Abu Bakar, Kamariah (Universiti Putra Malaysia Press, 2012)
The aim of the study was to determine the conditions that facilitate the implementation of online learning technology among faculty members at e-learning centres in Iranian universities. Research sample comprised of 220 faculty members who were randomly selected from nine public universities in Iran. Using the survey methodology, data were gathered through the use of a questionnaire. The questionnaire included the following: (a) 10 items pertaining to demographic information; and (b) 40 items related to Ely’s conditions facilitating technology implementation. The reliability of the scale was .91. The data were descriptively analyzed in the forms of mean and standard deviation using the Statistical Package for the Social Science (SPSS) version 16. Findings of the study showed that five conditions, which facilitate implementation of online learning technology, perceived to be present by the faculty members were: (a) dissatisfaction with the status quo, (b) existence of knowledge and skills, (c) availability of time, (d) existence of rewards or incentives, and (e) expected and encouraged participation. From these five conditions, `dissatisfaction with status quo’ was perceived to be the most present condition. On the other hand, three other conditions were perceived to be less present, namely, `commitment by those who are involved’, `leadership’, and `availability of resources’. From these three conditions, `availability of resources’ was perceived to be the most lacking at e-learning centres in Iranian universities.